Status of astronomy Outreach in Chile - Char, Farid (TECCIENCIA, 2020)
Currently, astronomy outreach in Chile is in good health. There is at least a dozen research groups belonging to universities, and most of them also include a speciﬁc area for Education and Public Outreach (EPO), using resources to communicate astronomy to the public. Ama- teur astronomy, astrotourism and astronomy clubs at schools are also important actors in astronomy outreach, as well as recent initiatives from the government recognizing the dark skies as our natural her- itage, and promoting science as a useful tool for knowledge and de- velopment. This presentation summarizes some of these initiatives, focusing on creating new educative materials establishing alliances, and ﬁnally discussing how these eﬀorts could consolidate the leader- ship of Chile in astronomy education, and how we could create new opportunities in South America on this topic.